2016
DOI: 10.18203/2394-6040.ijcmph20161361
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive cross-sectional study to assess prevalence of malnutrition in school children 6-14 years of age in rural and urban area of Bikaner, Rajasthan, India

Abstract: Economic growth alone, though impressive will not reduce malnutrition sufficiently to meet nutrition target. End hunger, achieve food security and improved nutrition ABSTRACT Background: Malnutrition affects the child's physical and cognitive growth and increases the susceptibility to infections consecutively having an adverse impact on economic growth of the country indirectly therefore with 39% of the world's malnourished living in India, we face a double jeopardy of malnutrition. The objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
2
4
0
Order By: Relevance
“…(Continued) prevalence in urban than rural is in line with findings in Lagos Nigeria (15.1% urban, 13.2% rural), Anambra Nigeria (6.5% urban, 1.7% rural) and Rajasthan India (1.11% urban, 0.28% rural)[41][42][43]. The overall prevalence rate of 4.9% in this study is lower to an earlier study done in Ekiti State with overweight prevalence of 13.8%[48].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…(Continued) prevalence in urban than rural is in line with findings in Lagos Nigeria (15.1% urban, 13.2% rural), Anambra Nigeria (6.5% urban, 1.7% rural) and Rajasthan India (1.11% urban, 0.28% rural)[41][42][43]. The overall prevalence rate of 4.9% in this study is lower to an earlier study done in Ekiti State with overweight prevalence of 13.8%[48].…”
supporting
confidence: 85%
“…underweight in this study is slightly higher in rural communities (6.5%) than in the urban community (6.3%). Higher prevalence of underweight in rural communities than urban were observed in study done among primary school children in urban and rural communities of Lagos State Nigeria, Anambra State Nigeria and Rajasthan India where underweight prevalence reported in rural settings (49.6%, 18.8% and 20.56% respectively) are higher than the urban rates (15.1%, 2.7% and 18.89% respectively) [41][42][43].…”
Section: Plos Onementioning
confidence: 99%
“…The prevalence of thinness was 48% in a study conducted by Mandal et al in a slum area of Kolkata and the prevalence of thinness was 29% in a study done by Fazili et al in Kashmir and it was 22% in a study done by Kumawat et al in Rajasthan. [7][8][9] This slight higher prevalence of underweight in the present study may be attributed to increasing level of knowledge and consciousness about overweight among the study participants living in an urban area than those living in slum area and rural areas.…”
Section: Discussionmentioning
confidence: 75%
“…Sati and Dahiya (2012) reported that the situation of malnutrition in children is also grave in Haryana as according to National Family Health Survey (2005)(2006), the prevalence of wasted, stunted and underweight children was 19.1 %, 45.7 % and 39.5 % respectively. Kumawat et al, (2016) conducted a study on 720 school children in the age group 6 to 14 years from urban and rural areas in Bikaner district of Rajasthan from July 2014-December 2014 with the objective to assess prevalence and types of malnutrition. The study tool used was a pre-tested questionnaire.…”
Section: Issn: 2319-7706 Volume 9 Number 8 (2020)mentioning
confidence: 99%
“…Very few (0.67 %) of the children were having obese grade I (BMI 25.0-30.0). Kumawat et al, (2016) conducted a study on 720 school children of Bikaner, Rajasthan and found that thinness and obesity (based on BMI-for-age) was seen in 22.22 per cent and 1.95 per cent children respectively. Hence, overall prevalence of malnutrition was found 24.17 per cent.…”
Section: Nutritional Status Of Primary School Childrenmentioning
confidence: 99%